Electric contact conducting element based on gallium-based liquid metal and preparation method thereof
By applying gallium-based liquid metal conductive paste to the surface of the electrical contact conductive element to fill the rough peak gap at the interface, the problem of insufficient current-carrying friction performance of the electrical contact conductive element is solved, and a significant increase in the current-carrying area and the improvement of the current transmission capability are achieved.
Patent Information
- Application Number
- CN202510293383.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing electrically contacted conductive components are difficult to effectively improve current-carrying friction performance, resulting in limited current-carrying capacity and shortened equipment life.
By applying gallium-based liquid metal conductive paste to the surface of the electrically contacted conductive element, the rough peak gap of the interface is filled and the actual current-carrying area is increased, thereby improving the interface current transmission capability.
It significantly reduces the contact resistance and friction coefficient, increases the actual current carrying area of the interface, and improves the ultimate current carrying capacity and performance stability of the electrical contact interface.
Smart Images

Figure CN119812812A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrical contact, and relates to an electrical contact conductive element and a preparation method thereof. Specifically, the present invention relates to an electrical contact conductive element comprising a gallium-based liquid metal conductive paste coating and a preparation method thereof. Background Art
[0002] Electrical contact refers to the transmission of current between conductive elements in contact with each other to achieve power or signal transmission. It is a key link that is widely present in power and electronic equipment. Electrical contact components include conductive slip rings of satellite solar array drive devices, high-speed rail pantographs / contact networks, micro-electromechanical system switches, etc. When the circuit structure and heat dissipation conditions are certain, the conductivity and current-carrying area of the material determine the current carrying capacity of the electrical contact system. Excessive current will cause material overheating, arc erosion, increased wear and further deterioration of the electrical contact state, shortening the life of electrical equipment and even causing serious accidents such as circuit burnout and power supply failure.
[0003] In order to achieve switch state switching and current transmission at the friction interface, the electrical contact point cannot be welded or crimped, but can only be achieved by contacting two conductive elements and applying a certain pressure. The actual material surface is composed of multiple uneven rough peaks. Under a small contact pressure, the actual current-carrying area of the interface is much smaller than the macro contact area, while a large contact pressure will increase wear and shorten the life. Figure 1 The current transmission of the electrical contact interface under the prior art is shown. Figure 1 It can be seen that the actual current-carrying area only accounts for a small part of the macroscopic contact area, and the current can only be transmitted between a small number of contacting rough peaks, and there is a high shrinkage resistance at the contact interface. The bulk current density of conventional wire materials such as copper can reach ~1kA / cm 2 However, due to the limitation of the actual current-carrying area, the current density of the electrical contact element can only reach ~10A / cm 2 , which is 1% of the bulk current carrying capacity. Therefore, the interface greatly restricts the current transmission, and the actual current-carrying area greatly restricts the improvement of the maximum current carrying capacity of the electrical contact material.
[0004] In order to ensure reliable transmission of current, the cross-sectional area of the contact parts of traditional technology is much larger than that of the transmission wire. At the same time, due to the limitation of the spatial size of the equipment, the macroscopic contact area cannot be increased indefinitely, which limits the improvement of the current carrying capacity of the electrical contact system. In addition, under the combined action of the mechanical-thermal-electrical effect, the microscopic physical / chemical state of the electrical contact interface undergoes dynamic evolution. Especially when the current carrying capacity is large, the mechanical / electrical performance of the interface deteriorates continuously during operation due to factors such as wear of rough peaks and arc erosion, which reduces the reliability of the long-term operation of the equipment.
[0005] Existing research on electrical contact materials focuses on improving the conductivity or lubrication properties of the material itself, sacrificing the wear resistance or conductivity of the material in exchange for improving other performance. The effect of improving the interface current transmission capacity is limited. Currently, there is no research to optimize its performance from the perspective of increasing the actual current-carrying area of the interface.
[0006] Liquid metal is currently used as a conductive medium in devices such as flexible circuits and conductive slip rings. However, liquid metal has strong fluidity and will react with most metals such as copper and silver. If liquid metal leaks due to failure of sealing components, it will cause serious problems such as corrosion of metal components and circuit short circuits. In addition, liquid metal has large surface tension and strong fluidity. When running at high speed, it will be separated from the electrode by centrifugal force, resulting in increased dynamic resistance fluctuations. When the temperature is lower than the melting point, liquid metal will solidify and become solid, causing moving parts to be welded. In addition, the bulk conductivity of liquid metal is not as good as that of metals such as copper, silver, and gold. The above problems greatly limit the application of liquid metal as a conductive medium. Summary of the invention
[0007] Problem that the invention aims to solve The object of the present invention is to provide an electrical contact conductive element and a preparation method thereof which can solve the problem that it is difficult to improve the current-carrying friction performance of the electrical contact conductive element.
[0008] Solutions for solving problems The present invention proposes the following design concept for the first time: by filling the interface roughness peak gap with a material having good deformation and conductivity, the actual current-carrying area of the interface of the electrical contact conductive element is increased, thereby improving the interface current transmission capacity. Specifically, the surface of the electrical contact conductive element of the present invention contains a gallium-based liquid metal conductive paste, which greatly increases the actual current-carrying area of the interface, making the actual current-carrying area almost equal to the macro contact area, thereby significantly improving the interface conductivity.
[0009] Specifically, the present invention provides an electrical contact conductive element, which comprises: a substrate; and a conductive paste coating formed on the substrate, wherein the conductive paste coating comprises gallium-based liquid metal and a conductive lubricant.
[0010] According to the electrical contact conductive element of the present invention, in the conductive paste coating, the content of the gallium-based liquid metal is 70 mass % to 90 mass %, and the content of the conductive lubricant is 10 mass % to 30 mass %.
[0011] According to the electrical contact conductive element of the present invention, the material used for the substrate is selected from at least one of oxygen-free copper, copper-chromium-zirconium, silver-copper, gold-nickel, aluminum-cobalt-chromium-iron-nickel, and niobium-molybdenum-tungsten alloy.
[0012] According to the electrical contact conductive element of the present invention, the gallium-based liquid metal is selected from at least one of pure gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy.
[0013] According to the electrical contact conductive element of the present invention, the conductive lubricant is selected from at least one of graphite, nickel ditelluride and niobium diselenide.
[0014] According to the electrical contact conductive element of the present invention, the particle size of the conductive lubricant is 1-200 μm.
[0015] The present invention also provides a method for preparing the electrical contact conductive element of the present invention, which comprises the following steps: (1) Preparing a conductive paste: mixing gallium-based liquid metal and conductive lubricant powder to obtain a conductive paste; (2) Applying conductive paste and flattening: applying the conductive paste obtained in step (1) on the surface of the substrate and flattening it, thereby forming a conductive paste coating layer on the surface of the substrate; (3) Sintering: Sintering the substrate coated with the conductive paste obtained in step (2) to obtain an electrical contact conductive element.
[0016] According to the preparation method of the present invention, step (1) is carried out at a temperature of 20-40°C.
[0017] According to the preparation method of the present invention, in step (2), before coating, the substrate to be coated is preheated at a temperature of 40-80°C.
[0018] According to the preparation method of the present invention, the sintering temperature of step (3) is 60-100° C., and the sintering holding time is 5-30 min.
[0019] Effects of the Invention The technical solution of the present invention has the following beneficial effects: 1) Compared with the prior art, the present invention reduces the mean and fluctuation of contact resistance and friction coefficient during current-carrying friction by using gallium-based liquid metal conductive paste. The contact resistance of the electrical contact conductive element of the present invention is significantly reduced in the current-carrying friction test, the friction coefficient is reduced, and the actual current-carrying area of the interface is increased.
[0020] 2) The electrical contact conductive element of the present invention can exhibit good current-carrying friction performance both in room temperature atmosphere and low temperature vacuum environment.
[0021] 3) The present invention reduces the fluidity of the liquid metal and its corrosion to the base material by mixing the gallium-based liquid metal with the conductive lubricant, thereby avoiding problems such as structural damage and circuit short circuit caused by liquid metal leakage.
[0022] 4) The electrical contact conductive element of the present invention has a significant effect on improving the interface current, a simple preparation method, strong practicability and versatility, and plays an important role in improving the electrical contact interface current transmission capacity. The electrical contact conductive element of the present invention can improve the limit current carrying capacity of the electrical contact conductive element, which is of great significance to the development of high-power equipment such as electric propulsion satellites and space solar power stations. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of current transmission at an electrical contact interface in the prior art.
[0024] Figure 2 It is a schematic diagram of current transmission at the electrical contact interface of the electrical contact conductive element of the present invention.
[0025] Figure 3 It is a comparison diagram of friction coefficient curves of the electrical contact conductive element-I and the comparative conductive element-I.
[0026] Figure 4 It is a comparison diagram of contact resistance curves of the electrical contact conductive element-I and the comparative conductive element-I.
[0027] Figure 5 It is the friction coefficient and contact resistance curve of the electrical contact conductive component-I under the load current friction test in the low temperature vacuum environment. DETAILED DESCRIPTION
[0028] Various exemplary embodiments, features and aspects of the present invention will be described in detail below. The word "exemplary" used here means "used as an example, embodiment or illustrative". Any embodiment described here as "exemplary" is not necessarily interpreted as being superior or better than other embodiments.
[0029] In addition, in order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0030] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0031] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0032] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0033] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoint numerical values A and B.
[0034] In this specification, "room temperature" means "20 to 40°C".
[0035] Electrical contact conductive element The present invention provides an electrical contact conductive element comprising a substrate and a gallium-based liquid metal conductive paste, wherein the gallium-based liquid metal conductive paste comprises a gallium-based liquid metal and a conductive lubricant. In this specification, the "electrical contact conductive element" is sometimes referred to as a "conductive element", the "gallium-based liquid metal conductive paste" is sometimes referred to as a "conductive paste", and the "gallium-based liquid metal" is sometimes referred to as a "liquid metal".
[0036] The electrical contact conductive element of the present invention uses a material with good deformation and conductivity to fill the gaps between the rough peaks of the interface, greatly increasing the actual current-carrying area. Specifically, gallium-based liquid metal and conductive lubricant are mixed with each other to prepare a conductive paste, and a small amount of the conductive paste is applied to the surface of the substrate. During the current-carrying friction process, the conductive paste is deformed under the action of force and fills into the gaps between the rough peaks to increase the actual current-carrying area of the interface. In addition, when the rough peaks on the two surfaces at the interface are separated due to wear or vibration, and the contact resistance increases, resulting in an increase in the Joule temperature rise, the conductive paste expands to adaptively suppress the separation of the electrical contact interface and improve the current transmission capacity of the interface.
[0037] Figure 2 The mechanism of the conductive paste containing gallium-based liquid metal increasing the actual current-carrying area and reducing the contact resistance is illustrated. Figure 2 It can be seen that the gallium-based liquid metal conductive paste is filled in the gaps between the rough peaks, making the actual current-carrying area almost the same as the macroscopic contact area, greatly improving the current transmission capacity of the interface.
[0038] Since the size of the rough peaks is small, with a height of only tens to hundreds of nanometers, only a very small amount of liquid metal is needed to fill the gaps between the rough peaks to significantly increase the actual current-carrying area; by adding conductive lubricants to the liquid metal, the surface tension and fluidity of the liquid metal can be reduced; the conductive lubricant in the conductive paste can be adsorbed on the surface of the substrate, exerting a lubricating effect while reducing the corrosion of the liquid metal on the substrate. Therefore, compared with the existing technology that uses a large amount of liquid metal as a conductive medium, applying the "liquid metal-conductive lubricant" conductive paste on the surface of the substrate not only achieves a significant increase in the actual current-carrying area, but also avoids problems such as liquid metal leakage, metal corrosion, separation from the electrode, and solidification.
[0039] Hereinafter, the electrical contact conductive element of the present invention will be described in detail.
[0040] Matrix The electrical contact conductive element of the present invention comprises a substrate. The material used for the substrate is not particularly limited, and can be any material commonly used in electrical contact, and is usually a metal with good electrical conductivity.
[0041] In some embodiments, the matrix material is preferably selected from at least one of oxygen-free copper, copper-chromium-zirconium, silver-copper, gold-nickel, aluminum-cobalt-chromium-iron-nickel, and niobium-molybdenum-tungsten alloy, and more preferably oxygen-free copper.
[0042] Gallium-based liquid metal conductive paste The electrical contact conductive element of the present invention comprises a gallium-based liquid metal conductive paste, wherein the gallium-based liquid metal conductive paste comprises a gallium-based liquid metal and a conductive lubricant.
[0043] The contact interface is subjected to mechanical load by the conductive lubricant, which separates the liquid metal from the substrate and reduces friction. The conductive paste can be filled around the load-bearing area as a current transmission path to achieve high conductivity and low friction current transmission.
[0044] The present invention improves the current transmission capacity of the electrical contact interface by increasing the actual current-carrying area, so it is necessary to fill a material with strong deformation ability and good conductivity into the rough peak gap. Gallium-based liquid metal has good fluidity and conductivity. By mixing it with a conductive lubricant, a conductive paste can be formed. This conductive paste has low corrosiveness to metals, can adaptively expand under the action of Joule temperature rise to inhibit the separation of rough peaks, and has good bonding with the metal matrix after sintering, which can effectively increase the actual current-carrying area of the interface.
[0045] <Gallium-based liquid metal> Liquid metal is a kind of metal with good fluidity and conductivity. Gallium-based liquid metal has attracted extensive attention in the fields of flexible electronics, soft robots, etc. due to its stable chemical properties, low melting point, and non-biological toxicity. In order to improve the interface current transmission capacity, the present invention fills the rough peak gap with gallium-based liquid metal to greatly increase the actual current-carrying area, thereby increasing the limiting current-carrying capacity of the electrical contact interface and reducing the dynamic contact resistance fluctuation.
[0046] In some embodiments, the gallium-based liquid metal is preferably selected from at least one of pure gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy, and more preferably pure gallium with a purity of >99.99%. In each of the gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy, the ratio of each metal element is not particularly limited.
[0047] In some embodiments, the content of gallium-based liquid metal in the conductive paste is 70 mass % to 90 mass %, for example, 72 mass %, 75 mass %, 77 mass %, 80 mass %, 82 mass %, 85 mass %, or 87 mass %.
[0048] <Conductive lubricant> Conductive lubricants can increase the viscosity of the conductive paste system, making the conductive paste system paste-like. Conductive lubricants can reduce the surface tension and fluidity of liquid metals. In addition, conductive lubricants can be adsorbed on the surface of the substrate, exerting a lubricating effect while reducing the corrosion of the liquid metal to the substrate.
[0049] In some embodiments, the conductive lubricant is preferably selected from at least one of graphite, nickel ditelluride, and niobium diselenide, and more preferably graphite.
[0050] In some embodiments, the content of the conductive lubricant in the conductive paste is 10 mass % to 30 mass %, for example, 13 mass %, 15 mass %, 18 mass %, 20 mass %, 23 mass %, 25 mass %, or 28 mass %.
[0051] In some embodiments, the particle size of the conductive lubricant is preferably 1-200 μm, for example, 50 μm, 120 μm, or 180 μm.
[0052] When the electrical contact conductive element of the present invention is subjected to a current-carrying friction test with a brass ball with a diameter of 8 mm in room temperature atmosphere and low-temperature vacuum environment, the friction coefficient fluctuates between 0.20 and 0.55 in room temperature atmosphere, and the contact resistance is <1 mΩ; the friction coefficient fluctuates between 0.20 and 0.50 in low-temperature vacuum, and the contact resistance is <8 mΩ, showing very low contact resistance fluctuations, indicating that the actual current-carrying area is significantly increased.
[0053] The parameters of the current-carrying friction test are: the motion mode is continuous rotation, the load is 1.5N, the current is 2A, the sliding linear speed is 10mm / s, the temperature of the room temperature atmosphere is 27℃, the temperature of the low temperature vacuum environment is -153℃, and the vacuum degree is <1×10 - 3 Pa.
[0054] During the current-carrying friction process, even if the substrate is worn, the conductive paste can still fill the rough peak gaps in the wear scar area, avoiding arc erosion and the reduction of the actual current-carrying area, reducing the contact resistance and its fluctuations, alleviating the problem of increased material wear caused by Joule heat temperature rise, and greatly improving the performance of the electrical contact interface.
[0055] Method for preparing electrical contact conductive element The present invention also provides a method for preparing an electrical contact conductive element, the method comprising the following steps: (1) Preparing a conductive paste: mixing gallium-based liquid metal and conductive lubricant powder to obtain a conductive paste; (2) Applying conductive paste and flattening: applying the conductive paste obtained in step (1) on the surface of the substrate and flattening it, thereby forming a conductive paste coating layer on the surface of the substrate; (3) Sintering: Sintering the substrate coated with the conductive paste obtained in step (2) to obtain an electrical contact conductive element. Each step is described in detail below.
[0056] (1) Preparation of conductive paste In this step, the gallium-based liquid metal and the conductive lubricant powder are uniformly mixed in a desired proportion by mechanical stirring to obtain a conductive paste, thereby reducing the fluidity of the liquid metal and the corrosiveness to the substrate while maintaining the strong deformation ability of the gallium-based liquid metal.
[0057] During the mixing process, the conductive lubricant powder is preferably added to the gallium-based liquid metal in small amounts multiple times, and mechanical stirring is continuously performed to uniformly mix the graphite powder in the liquid metal. During the stirring process, as the amount of graphite mixed increases, the viscosity of the mixed system increases and gradually changes from liquid to paste, so as to prepare a conductive paste with uniform composition.
[0058] In some embodiments, the gallium-based liquid metal is preferably pure gallium with a purity of >99.99%. In this case, since the melting point of pure gallium is 29.8°C, it needs to be heated to melt in order to be mixed with the conductive lubricant.
[0059] In some embodiments, the conductive lubricant is preferably graphite powder.
[0060] In some embodiments, the temperature of this step is 20-40° C., such as 25° C., 30° C., or 35° C., to avoid excessively high temperature that accelerates oxidation of the liquid metal.
[0061] The conductive paste prepared by this step exhibits good deformation ability at room temperature and does not flow spontaneously, thus avoiding problems caused by liquid metal leakage.
[0062] (2) Apply conductive paste and flatten The "liquid metal-conductive lubricant" conductive paste obtained in step (1) is evenly coated on the surface of the substrate to be coated, thereby forming a uniform conductive paste coating on the substrate surface. During the coating process, it is preferred to evenly apply normal pressure so that the conductive paste spreads on the substrate surface under the extrusion effect, and a small amount of liquid metal is squeezed out of the conductive paste and combined with the substrate material, thereby forming a conductive paste coating on the substrate surface that can be deformed under the action of external force.
[0063] The obtained substrate coated with the conductive paste coating is repeatedly squeezed multiple times to remove excess conductive paste on the surface of the substrate, leaving only a small amount of conductive paste coating tightly bonded to the substrate, and making the surface of the substrate coated with the conductive paste coating smooth, that is, making the surface of the substrate coated with the conductive paste coating smooth on a macroscopic basis.
[0064] In some embodiments, the substrate to be coated is preferably preheated at a temperature of 40-80°C, such as 50°C, 60°C, or 70°C.
[0065] (3) Sintering The substrate coated with the conductive paste obtained in step (2) is sintered to enhance the bonding force between the conductive paste and the substrate, so that the conductive paste coating is smoother and more tightly bonded to the substrate, and finally an electrical contact conductive element is obtained.
[0066] In some embodiments, it is preferred to perform sintering with a weight placed on the substrate coated with the conductive paste coating.
[0067] In some embodiments, the sintering temperature is preferably 60-100°C, for example, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, and the sintering holding time is preferably 5-30 min, for example, 10 min, 15 min, 20 min, 25 min.
[0068] The preparation method described in the present invention utilizes the characteristics of gallium-based liquid metal conductive paste, which has strong deformation ability and certain lubrication ability, and fills it into the rough peak gaps on the surface of the electrical contact conductive element by a method of sintering after coating. When the electrical contact conductive element prepared by the present invention is subjected to a current-carrying friction test to evaluate the performance of the electrical contact interface, during the contact and friction process, the conductive paste deforms under the action of contact and shear force, and fills into the rough peak gaps of the interface, so that the actual current-carrying area is almost the same as the macro contact area. In addition, the conductive lubricant in the conductive paste is adsorbed on the surface of the substrate, plays the role of carrying and isolating the liquid metal from the substrate, and improves the problem of liquid metal loss and reduced mechanical strength of the substrate caused by the reaction between the liquid metal and the substrate. Example
[0069] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially. The test methods not described in detail in the examples are all conventional test methods in the art.
[0070] Example 1
[0071] Here, the gallium-based liquid metal is pure gallium with a purity of >99.99%; the conductive lubricant is graphite with a particle size of 120 μm and a purity of >99.9%; and the matrix material is an oxygen-free copper sample block with a diameter of 30 mm.
[0072] The electrical contact conductive element-I of Example 1 was prepared according to the following method. The equipment used in the preparation process are those known to those skilled in the art.
[0073] (1) First, weigh 1.5g of graphite powder, add a small amount of it into a plastic can and spread it on the wall of the container to reduce the direct contact between the liquid metal added later and the wall, and avoid uneven mixing caused by residual liquid metal on the wall surface. After heating the pure gallium to melt, use a pipette to add 1ml of pure gallium into the plastic can, and continuously stir the above mixed system mechanically to prevent the liquid pure gallium from re-solidifying. During the stirring process, add the weighed graphite powder to the mixed system several times in small amounts so that the graphite powder is evenly dispersed inside the pure gallium. During stirring, control the temperature of the mixed system at 20~40℃ to avoid excessive temperature accelerating the oxidation of pure gallium. After sufficient stirring, the "pure gallium-graphite" conductive paste is prepared.
[0074] (2) Place the oxygen-free copper sample on a heating table at 40°C for preheating, take a small amount of conductive paste with a blade and apply it on the surface of the oxygen-free copper sample, and manually apply pressure to the conductive paste on the surface of the oxygen-free copper sample through a glass slide, so that it spreads into a uniform conductive paste coating on the surface of the oxygen-free copper sample. When pressure is applied to the conductive paste, a small amount of gallium inside the conductive paste is squeezed out and combined with the oxygen-free copper below, increasing the bonding force between the conductive paste coating and the substrate.
[0075] The excess conductive paste squeezed out from the edge of the oxygen-free copper sample during the coating process is removed until only a small amount of conductive paste coating that is tightly bonded to the oxygen-free copper sample and macroscopically smooth remains on the surface of the oxygen-free copper sample.
[0076] (3) A heavy object was placed on the surface of the oxygen-free copper sample coated with a conductive paste coating, and the temperature of the heating table was raised to 100°C and kept for 15 minutes for sintering, and then naturally cooled to enhance the bonding between the conductive paste coating and the substrate, and finally an electrical contact conductive element was obtained, which was recorded as electrical contact conductive element-I.
[0077] In the electrical contact conductive element-I, the conductive paste coating does not show fluidity even at temperatures higher than the melting point of liquid metal involved in the use of the conductive element, such as 70°C, thereby avoiding the leakage problem of liquid metal while maintaining good deformation and conductivity, and being able to provide a large amount of additional actual current-carrying area in the rough peak gaps.
[0078] Comparative Example 1 An oxygen-free copper sample whose surface is not coated with a conductive paste coating is used as a comparative conductive element, and is recorded as comparative conductive element-I.
[0079] Current-carrying friction test A brass ball (grade H62) with a diameter of 8 mm was used as a grinding pair, and a current-carrying friction test was performed on the electrical contact conductive element-I and the comparative conductive element-I to evaluate the performance of the electrical contact interface. The tests were carried out in room temperature atmosphere and low temperature vacuum environment to verify the versatility of the method proposed in the present invention. The test conditions were: the motion mode was continuous rotation, the load was 1.5 N, the current was 2 A, the sliding linear speed was 10 mm / s, the room temperature atmospheric environment temperature was 27 ° C, the air pressure was 101 kPa, and the low temperature vacuum environment temperature was -153 ° C, the air pressure <1×10 -3 Pa. During the test, the changes in the friction coefficient and contact resistance of the electrical contact system are recorded in real time.
[0080] According to the test results of the electrical contact conductive element-I and the comparative conductive element-I, the effect of the conductive paste on improving the interface current transmission capacity is explained. Figure 3 and Figure 4The changes in the friction coefficient and contact resistance of the electrical contact conductive element-I and the comparison conductive element-I during the current-carrying friction process were compared respectively. The average values and fluctuation amplitudes of the friction coefficient and contact resistance of the electrical contact conductive element described in the present invention were significantly reduced, which indicates that the conductive lubricant in the conductive paste has played a lubricating role, and the conductive paste can effectively fill the gaps between rough peaks and reduce the contact resistance and its fluctuations.
[0081] To further illustrate the universality of the present invention, the electrical contact performance of the electrical contact conductive element-I was tested in a low temperature vacuum environment. The results are as follows: Figure 5 The test results show that even at -153°C, which is far below the melting point of gallium-based liquid metal, the electrical contact system can still operate effectively and has a low contact resistance, indicating that under the action of local Joule heat at the contact interface, the conductive paste maintains good deformation ability and plays a role in increasing the actual current-carrying area.
[0082] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.
[0083] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrical contact conductive element, characterized in that: The electrical contact conductive element comprises: matrix; and forming a conductive paste coating on the substrate, Wherein, the conductive paste coating contains gallium-based liquid metal and conductive lubricant.
2. The electrical contact conductive element according to claim 1, characterized in that: In the conductive paste coating, the content of the gallium-based liquid metal is 70 mass % to 90 mass %, and the content of the conductive lubricant is 10 mass % to 30 mass %.
3. The electrical contact conductive element according to claim 1 or 2, characterized in that: The material used for the substrate is selected from at least one of oxygen-free copper, copper-chromium-zirconium, silver-copper, gold-nickel, aluminum-cobalt-chromium-iron-nickel, and niobium-molybdenum-tungsten alloy.
4. The electrical contact conductive element according to claim 1 or 2, characterized in that: The gallium-based liquid metal is selected from at least one of pure gallium, gallium-indium alloy, gallium-indium-tin alloy and gallium-indium-tin-zinc alloy.
5. The electrical contact conductive element according to claim 1 or 2, characterized in that: The conductive lubricant is selected from at least one of graphite, nickel ditelluride and niobium diselenide.
6. The electrical contact conductive element according to claim 1 or 2, characterized in that: The particle size of the conductive lubricant is 1-200 μm.
7. A method for preparing an electrical contact conductive element according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparing a conductive paste: mixing gallium-based liquid metal and conductive lubricant powder to obtain a conductive paste; (2) Applying conductive paste and flattening: applying the conductive paste obtained in step (1) on the surface of the substrate and flattening it, thereby forming a conductive paste coating layer on the surface of the substrate; (3) Sintering: Sintering the substrate coated with the conductive paste obtained in step (2) to obtain the electrical contact conductive element.
8. The preparation method according to claim 7, characterized in that: The step (1) is carried out at a temperature of 20-40°C.
9. The preparation method according to claim 7 or 8, characterized in that: In the step (2), the substrate to be coated is preheated before coating, and the preheating temperature is 40-80°C.
10. The preparation method according to claim 7 or 8, characterized in that: The sintering temperature of step (3) is 60-100° C., and the sintering holding time is 5-30 min.
Citation Information
Patent Citations
Liquid-state metal electronic paste and preparation method thereof
CN107452436A
Liquid metal conductive coating and preparation method and application thereof
CN109627829A
Oxidation-resistant conductive paste composition, conductive coating and preparation method thereof
CN110246605A
Conductive paste, preparation method thereof, wearable electronic circuit and DIY kit of wearable electronic circuit
CN111462934A
The lubrication of electrical contact members
GB1045094A
Cited By
A negative wear ultra-wear current carrying friction pair material
CN120400742B
High-precision chip resistor capable of being quickly disassembled
CN122474442A